Autophagosomes take the Klp98-A train. (2nd January 2017) - Mauvezin, Caroline; Neufeld, Thomas P.
ABSTRACT: The intracellular movement of membrane-bound vesicles is closely tied to their formation, maturation and ultimate function within the cell. Motor proteins and their associated cytoskeletal networks are critical for vesicle transport, but whether these factors play a more direct role in vesicle biogenesis is unclear. In recent work, we found that the Drosophila kinesin proteins Khc and Klp98A are both required for the normal anterograde movement of autophagosomes and autolysosomes during starvation-induced autophagy. In addition, Klp98A has a transport-independent function of promoting autophagosome-lysosome fusion, a key step in the maturation of autophagic vesicles. This function correlates with the association of Klp98A with the autophagosomal protein Atg8 and with the endolysosomal protein Rab14, suggesting that Klp98A may promote vesicle fusion by physically linking these vesicle surface proteins. These findings demonstrate how the delivery of vesicles to their proper destination can be coordinated with additional steps in their life cycle through molecular motor-based interactions.